2006
DOI: 10.1097/01.ta.0000199913.02341.d6
|View full text |Cite
|
Sign up to set email alerts
|

Closed, Locked Intramedullary Nailing of Pediatric Femoral Shaft Fractures Through the Tip of the Greater Trochanter

Abstract: This study showed that with strict adherence to a surgical technique that respects the growing proximal femur and its vascular anatomy, using the tip of the greater trochanter as an entry point to the femoral canal, the proven advantages of closed, intramedullary nailing can safely be offered to the adolescent patient population as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 25 publications
1
33
0
1
Order By: Relevance
“…Although we did not note any instance of osteonecrosis of the femoral head in our group, that is a potentially catastrophic complication 3,20,21 . The recent introduction of trochanteric nails may address this risk 22 , but there is at least one documented case report of osteonecrosis of the femoral head after use of a trochanteric entry point 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not note any instance of osteonecrosis of the femoral head in our group, that is a potentially catastrophic complication 3,20,21 . The recent introduction of trochanteric nails may address this risk 22 , but there is at least one documented case report of osteonecrosis of the femoral head after use of a trochanteric entry point 23 .…”
Section: Discussionmentioning
confidence: 99%
“…This method has yielded good results, but most of the studies were performed on adult subjects [16][17][18]44]. One study showed that rigid nail insertion through the greater trochanter in adolescents results in satisfactory patient outcomes, although the nails used for this study were designed for insertion through the piriformis fossa [26]. In a case series of 78 patients, the use of a modified rigid humeral nail inserted laterally to the trochanteric tip has been shown to be effective with few complications [27].…”
Section: Discussionmentioning
confidence: 99%
“…When ESINs are used, there is an increased incidence of malunion and limb length discrepancy, in addition to pain and irritation at the implant insertion site [1,34]. The use of more rigid nails designed for antegrade insertion through the piriformis fossa has largely been abandoned because of the potential for AVN of the femoral head, a devastating complication with lifelong consequences [24,26,27,43]. The potential for this complication can be avoided by inserting the nail through the greater trochanter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For most patients younger than 5 years old, the initial treatment of choice is with hip spica with or without initial traction, which can give satisfactory results [4], while in older patients conservative treatment provides less satisfactory results [5,6]. In adolescent patients, nonoperative treatment does not always ensure complete fracture site rotational and translational stability, often resulting in angular and rotational deformities as well as in limb length discrepancy [7].…”
Section: Introductionmentioning
confidence: 99%